The value of ultrasound guided laser ablation in papillary thyroid recurrence carcinoma: A retrospective, single center study from China - Yong-ping, Liang; Juan, Zhang; Li, Jing-wu; Qi, Huai-hua; Liu, Jing-ping; Zhao, Yong-feng; Liu, Wen-gang; Zhang, Xing-hao; Zhou, Ping (Frontiers in Endocrinology, 2022)
Objective: The efficacy and safety of ultrasound-guided percutaneous laser ablation (PLA) for treating recurrent papillary thyroid cancer nodules (RPTCNs). Methods: A retrospective study was conducted in 43 patients with single recurrent thyroid cancer which was diagnosed by fine needle aspiration biopsy (FNAB). The extent of ablation was assessed by contrast-enhanced ultrasound (CEUS) 24h after PLA. At baseline (before ablation), 6, and 12 months, and every 6 months thereafter, the following were recorded: nodule maximum diameter, volume reduction rate (VRR), complications, and side effects. Result: All 43 patients were successfully treated with PLA without serious complications. All patients underwent CEUS 24 hours after PLA treatment, and all achieved complete ablation. The success rate of single ablation was 100%. The average follow-up time was 23.47 ± 6.50 months, 12 ~ 36 months. At the last follow-up, 32 (74.4%) ablation lesions disappeared completely and 11 (25.6%) ablation lesions showed scar-like changes. No lymph node metastasis was found during follow-up. The maximum diameter and volume of nodules decreased from 5.1 ± 1.4 mm, 86.22 ± 20.46 mm3 before operation to 0.73 ± 1.1 mm, 1.02 ± 1.92 mm3 at the end of observation (P < 0.01). The average volume reduction rates (VRR) at 6, 12, 18, 24, 30 and 36 months after ablation were 11.92%, 60.64%, 82.26%, 90.96%, 93.7% and 97.79% respectively. No regrowth of treated nodule and distant metastases were detected. One patient (2.3%) had local recurrence and was treated with PLA again. Conclusion: Ultrasound-guided PLA appears to be effective and safe for treating unifocal RPTCNs in selected patients who are ineligible for surgery, which is suitable for clinical application and promotion.